Biomimetic melatonin-loaded silk fibroin/GelMA scaffold strengthens cartilage repair through retrieval of mitochondrial functions. (20th May 2023) - Hou, Mingzhuang; Zhang, Yijian; Liu, Yang; Ge, Xiaoyang; Hu, Xiayu; Zhao, Zhijian; Tian, Xin; Liu, Tao; Yang, Huilin; Chen, Xi; He, Fan; Zhu, Xuesong
Highlights: SF-GelMA@MT scaffold was fabricated with aqueous-based procedures plus photocurable surface modification. Prolonged released melatonin facilitated cartilage ECM production via mitochondrial enhancement. Activated SIRT1-SOD2 signaling pathway was implicated in SF-GelMA@MT-induced chondroprotective effects. In situs implantation of SF-GelMA@MT promoted cartilage regeneration in full-thickness cartilage defect model. Abstract: Articular cartilage injury induced by collision or trauma is a common sports-related condition that may progress to pain, dysfunction, and secondary osteoarthritis (OA). Limited by self-renewal potential, cartilage regeneration faces a quandary while bio-inspired novel strategies are urgently required. In this study, by a soft freezing method and surface modification technique, a multi-functional silk fibroin (SF) plus gelatin methacrylate (GelMA) scaffold laden with melatonin (MT) was prepared. SF-GelMA@MT scaffold demonstrated enhanced biomechanical characteristics and long-acting melatonin release. In vitro treatment with SF-GelMA@MT induced the synthesis of cartilage extracellular matrix (ECM) components. Mechanistically, sustained release of melatonin yielded robust chondroprotective effects via improving mitochondrial polarization and antioxidant properties. SF-GelMA@MT implantation boosted cartilage renascence in a full-thickness cartilage defect model via mitochondria-associated sirtuins 1 (SIRT1)-superoxide dismutase 2 (SOD2) signaling pathway in vivo . In summary, this research proposed a well-designed bionic composite scaffold that promotes cartilage regeneration via mitochondrial function enhancement, which is of tremendous potential for cartilage tissue engineering.